A consortium of seven commensal bacteria promotes gut microbiota recovery and strengthens ecological barrier against vancomycin-resistant enterococci - Alan Jan; Perrine Bayle; Nacer Mohellibi; Clara Lemoine; Frédéric Pepke; Fabienne Béguet-Crespel; Isabelle Jouanin; Marie Tremblay-Franco; Béatrice Laroche; Pascale Serror; Lionel Rigottier-Gois (Microbiome)
Abstract Background Vancomycin-resistant enterococci (VRE) often originate from the gastrointestinal tract, where their proliferation precedes dissemination into the bloodstream, and can lead to systemic infection. Uncovering the actors and mechanisms reducing the intestinal colonisation by VRE is essential to control infection. We aimed to identify commensal bacteria that interfere with VRE gut colonisation or act as an ecological barrier. Results We performed a 3-week longitudinal analysis of the gut microbiota composition and VRE carriage levels during microbiota recovery in mice colonised with VRE after antibiotic-induced dysbiosis. By combining biological data and mathematical modelling, we identified 15 molecular species (OTUs) that negatively correlated with VRE overgrowth. Six strains representative of these OTUs were collected, cultivated and used in mixture with a seventh strain (Mix7) in two different mouse lines challenged with VRE. Of the seven strains, three belonged to Lachnospiraceae, one to Muribaculaceae, one to Ruminococcaceae and two to Lactobacillaceae. We found that Mix7 led to a better recovery of the gut microbiota composition and reduced VRE carriage. Differences in the effect of Mix7 were observed between responder and non-responder mice. These differences were associated with variations in the composition of the initial microbiota and during recovery and represent potential biomarkers for predicting response to Mix7. In a mouse model of alternative stable state of dysbiosis, response to Mix7 was associated with higher concentrations of short-chain fatty acids (acetate, propionate, butyrate) and a range of metabolites including bile acids, reflecting the recovery of the microbiota back to initial state. Furthermore, Muribaculum intestinale strain was required to obtain the Mix7 effect on VRE reduction in vivo, but the presence of at least one of the other six strains was needed. None of the supernatant of the seven strains, alone or in combination, inhibited VRE growth in vitro. Interestingly, five strains belong to species shared among humans and mice, and the other two have human functional equivalents. Conclusions An innovative approach based on mathematical modelling of the microbiota composition permitted to identify a mixture of commensal bacterial strains, which improves the ecological barrier effect against VRE. The mechanisms are dependent on the recovery and initial composition of the microbiota. Ultimately, this work will enable a move towards a personalised medicine by targeting predisposed patients presenting a risk of infection, such as neutropenic or bone-marrow transplant patients, and likely to respond to supplementation with commensal strains, providing new live biotherapeutic products and biomarkers to predict response to supplementation. Video Abstract